2022
DOI: 10.1016/j.biopha.2021.112243
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of novel aureobasidium pullulans strains produced beta-1,3-1,6 glucans on interleukin-6 and D-dimer levels in COVID-19 patients; results of a randomized multiple-arm pilot clinical study

Abstract: Objective In this pilot clinical study, we report the beneficial effects of beta glucans derived from two strains AFO-202 and N-163 of a black yeast Aureobasidium pullulans on the biomarkers for cytokine storm and coagulopathy in COVID-19 patients. Methods A total of 24 RT-PCR positive COVID-19 patients were recruited and randomly divided into three groups (Gr): Gr. 1 control (n=8) – Standard treatment; Gr. 2: Standard treatment + AFO-202 beta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 28 publications
0
41
0
Order By: Relevance
“…Recently, the valuable beneficial effects of beta glucans, derived from two strains AFO-202 and N-163 of a black yeast Aureobasidium pullulans , were described. They were evaluated on the biomarkers for cytokine storm and coagulopathy in COVID-19 patients, in a randomized pilot clinical study, where the supplementation with these beta glucans helped to maintain the major biomarkers of clinical severity and mortality of COVID-19, such as IL-6, D-Dimer, neutrophil to lymphocyte ratio (NLR) over 15 and 30 days, compared to those who underwent standard care alone [ 154 ]. Another recent pilot study, an open label, randomized clinical trial, investigated the potential benefit of calcitriol therapy given to 50 patients hospitalized with COVID-19 indicating an improvement in oxygenation, suggesting the need for a larger randomized trial [ 155 ].…”
Section: Recent Clinical Studiesmentioning
confidence: 99%
“…Recently, the valuable beneficial effects of beta glucans, derived from two strains AFO-202 and N-163 of a black yeast Aureobasidium pullulans , were described. They were evaluated on the biomarkers for cytokine storm and coagulopathy in COVID-19 patients, in a randomized pilot clinical study, where the supplementation with these beta glucans helped to maintain the major biomarkers of clinical severity and mortality of COVID-19, such as IL-6, D-Dimer, neutrophil to lymphocyte ratio (NLR) over 15 and 30 days, compared to those who underwent standard care alone [ 154 ]. Another recent pilot study, an open label, randomized clinical trial, investigated the potential benefit of calcitriol therapy given to 50 patients hospitalized with COVID-19 indicating an improvement in oxygenation, suggesting the need for a larger randomized trial [ 155 ].…”
Section: Recent Clinical Studiesmentioning
confidence: 99%
“…β-Glucans can thus serve as effective immune-modulatory agents in sepsis, as they possess all four capabilities outlined above for sepsis management: mounting an anti-infection defense, immune suppression of proinflammatory cytokines, immune enhancement in the advanced immune-paralysis stage, and metabolic effects. Their potential as effective immunoadjuvants in sepsis can be observed from their effects in studies that have used them for COVID-19 ( 41 , 42 ). We will explain how COVID-19 is an accelerated sepsis-like reaction before we report the outcome of the studies of β-glucans in COVID-19, making them suitable treatment adjuvants in sepsis.…”
Section: Covid-19 and Sepsismentioning
confidence: 99%
“…In addition, their biological response-modifying actions also vary ( 29 ). We have previously shown that A. pullulans -derived β-glucans are secreted by black yeast as an exopolysaccharide, thereby negating isolation or extraction methods ( 41 , 42 , 49 ). Two different strains of A. pullulans , AFO-202 and N-163, produce β-glucan as an exo-polysaccharide with the same chemical composition (C6H10O5) n but a different structural formula.…”
Section: Use Of a Pullulans -Derived β-Glucans As ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Immunotherapies are at various stages of development aiming at augmented anticoronavirus immunity with a particular focus on the innate immune response to not only enhance it but also modulate it in a balanced manner to prevent hyperimmune activation (Schijns & Lavelle, 2020 ). Beta (β)‐glucans have been suggested to be potential nonspecific immunostimulatory adjuvants that can promote trained immunity (TRIM) to beneficially boost protective antiviral immunity apart from BCG vaccine (Geller & Yan, 2020 ), with clinical pilot studies have proven their efficacy and safety in bringing down the inflammatory and immune biomarkers associated with cytokine storm and coagulopathy in COVID‐19 patients (Pushkala et al, 2021 ; Raghavan et al, 2022 ).…”
mentioning
confidence: 99%